Association between anxiety and depression with chronic periodontitis - Shrestha, Sajeev; Sharma, Shivalal; Sapkota, Nidesh; Giri, Dhirendra K; Baral, Dharanidhar (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: It is thought that chronic stress negatively affects immune response efficacy which in turn cause an imbalance between host and parasite leading to periodontal breakdown. The study aims to investigate the association between anxiety and depression with chronic periodontitis. Materials & Methods: This was a cross sectional study comprising of 350 individuals of both sexes, above 25 years of age. The study population was divided into two groups. Group 2 consisted of those subjects with clinical attachment loss of ≥ 3 mm in at least 30% of site examined, and the samples that did not satisfy the above criteria were categorized into Group 1. Group 1 included 184 individuals while group 2 had 166 subjects. Clinical examinations were performed by a single examiner. Psychological instrument used was Hospital anxiety and depression scale (HADS). Chi square and student t test were performed to compare between the two groups. Results: The mean depression scores in Group 1 and Group 2 were 6.64 ± 2.58 and 7.90 ± 2.86, respectively while the mean anxiety scores of Group 1 and Group 2 were 7.76 ± 3.12 and 9.07 ± 3.08, respectively (p<001). Conclusion: Within the limits of this study it is possible to conclude that there was significant association between periodontitis and anxiety, and depression